Pengaruh Model Pembelajaran Kooperatif Learning Terhadap Perkembangan Sosial Emosional Dan Perkembangan Bahasa Anak TK - Halimatus Sa’diyah; Rudy Sumiharsono; Eges Triwahyuni (LP. Ma'arif Janggan Magetan, 2023)
The purpose of the research was to find out whether using cooperative learning can increase the creativity and language development of Group A students at TK Al Hidayah Tegalharjo. Variable X (cooperative learning) has 4 indicators, Y1 (social emotional development) has 5 indicators. Variable Y2 (Language development) has 7 indicators. The research design uses causal quantitative. The method for determining areas is purposive area sampling. The research population for the population research technique was 30 children from group A. Data collection techniques: 1). observation, 2). interview, 3). documentary. The results of the interview are then processed into several instrument tests from validity and reliability tests, then classic assumption tests including normality tests, homogeneity tests, autocorrelation tests, and heteroscedasticity tests, and finally hypothesis tests which include t tests and F tests. against Y1 sig<0.05 (0.000<0.05), X against Y2 sig<0.05(0.001<0.05), F. So it can be concluded that cooperative learning influences social emotional development and language development.